Pengaruh Profitabilitas, Inventory Intensity, dan Capital Intensity terhadap Tax Avoidance pada Perusahaan Sektor Energi yang Terdaftar di BEI Periode 2021–2024 - Indah Sukma Lestari; Rahma Maulidia; Khristina Yunita (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
Taxes are the main sources of state revenue that plays an important role in national development. However, tax avoidance practices are still a challenge, especially in the energi sector which vulnerable due the complexity of corporate structure and cross-border transactions. Factors such as profitability, inventory intensity, and capital intensity are thought to affect the company’s tedency to practice tax avoidance. This study aims to examine the effect of profitability, inventory intensity, and capital intensity on tax avoidance. The population in this study includes energy sector companies listed on Indonesian Stock Exchange (IDX) during the 2021-2024 period. This study uses a quantitative approach with secondary data obtained from the company’s financial statements. The sample selection was carried out using the purposive sampling, so that 27 companies were sampled, with a total of 108 observations Data analysis was performed using panel data regression with the support of Eviews 12 software. The analysis results indicate that profitability has a positive effect on tax avoidance, inventory intensity has a negative effect on tax avoidance, while capital intensity has no effect on tax avoidance.